2015
DOI: 10.1038/nchem.2344
|View full text |Cite
|
Sign up to set email alerts
|

Latent analysis of unmodified biomolecules and their complexes in solution with attomole detection sensitivity

Abstract: The study of biomolecular interactions is central to an understanding of function, malfunction and therapeutic modulation of biological systems, yet often involves a compromise between sensitivity and accuracy. Many conventional analytical steps and the procedures required to facilitate sensitive detection, such as the incorporation of chemical labels, are prone to perturb the complexes under observation. Here we present a 'latent' analysis approach that uses chemical and microfluidic tools to reveal, through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 49 publications
4
70
0
Order By: Relevance
“…The situation is dramatically different at pH 6, where fibrils can clearly be seen under all conditions, albeit very few in the presence of EGCG ox , where ThT fluorescence is completely suppressed. In order to obtain an independent measure for the degree of inhibition of aggregation by EGCG and EGCG ox , we centrifuged the samples after the aggregation experiment and quantified the average size and concentration ( Figure 4C) of the soluble protein by microfluidic diffusional sizing (MDS) [60,61] (see Methods section for details). We found that in the absence of EGCG, both at pH 7 and pH 6, the protein converts near-quantitatively into aggregates, whereas in the presence of EGCG and EGCG ox , nearly all of the protein remains soluble, and display average hydrodynamic radii of ∼2.3 nm at pH 6 and ∼2.7 nm at pH 7, indistinguishable from measurements of pure monomeric protein and in close agreement with previous measurements under similar solution conditions [62].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The situation is dramatically different at pH 6, where fibrils can clearly be seen under all conditions, albeit very few in the presence of EGCG ox , where ThT fluorescence is completely suppressed. In order to obtain an independent measure for the degree of inhibition of aggregation by EGCG and EGCG ox , we centrifuged the samples after the aggregation experiment and quantified the average size and concentration ( Figure 4C) of the soluble protein by microfluidic diffusional sizing (MDS) [60,61] (see Methods section for details). We found that in the absence of EGCG, both at pH 7 and pH 6, the protein converts near-quantitatively into aggregates, whereas in the presence of EGCG and EGCG ox , nearly all of the protein remains soluble, and display average hydrodynamic radii of ∼2.3 nm at pH 6 and ∼2.7 nm at pH 7, indistinguishable from measurements of pure monomeric protein and in close agreement with previous measurements under similar solution conditions [62].…”
Section: Resultsmentioning
confidence: 99%
“…FluidityOne is a microfluidic diffusional sizing (MDS, [60]) device, which measures the rate of diffusion under steady state, laminar flow. The protein concentration is determined by fluorescence intensity, as the protein is mixed with ortho-phthalaldehyde (OPA) after the diffusion, a compound which reacts with primary amines, producing a fluorescent compound [61].…”
Section: Microfluidic Diffusional Sizing and Concentration Measurementsmentioning
confidence: 99%
“…Such post-process labelling ensured that the physical properties determined in this way describe the unlabelled rather than the labelled state of the molecule or the complex. 63 Using this strategy the interactions could be described between α-synuclein monomers and nanobodies in their label-free states. Such microfluidic devices provide effective platforms for probing biomolecular processes and interactions in a label-free manner while ensuring that the molecules of interest can in principle be analysed at physiologically relevant concentrations.…”
Section: Interactions Between Amyloid Structures and Other Moleculesmentioning
confidence: 99%
“…[58][59][60][61][62] Changes to the size or charge of sample molecules upon complex formation can be explored to probe non-covalent protein-protein interactions and protein-ligand binding. 59,60,63,64 These microfluidic strategies can be, and have been, applied to characterise the properties of amyloid structures and their interactions with chemical compounds or other proteins. 60,62,63,65 Microfluidic methods have been applied succesfully to the highthroughput generation of microdroplets with highly uniform volumes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation